2012
DOI: 10.12816/0003115
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Methods of an Undergraduate Psychiatry Course at a Saudi University = أساليب تقييم مساق الطب النفسي للطلاب في جامعة سعودية

Abstract: Objectives: In Arab countries there are few studies on assessment methods in the field of psychiatry. The objective of this study was to assess the outcome of different forms of psychiatric course assessment among fifth year medical students at King Faisal University, Saudi Arabia. Methods: We examined the performance of 110 fifth-year medical students through objective structured clinical examinations (OSCE), traditional oral clinical examinations (TOCE), portfolios, multiple choice questions (MCQ), and a wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…Amr and Amin[1] showed non-significant differences in male and female attainment in psychiatry in our institute. Our subjective impressions and a previous study suggested that women had more positive attitude and performed better than males in King Faisal University.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…Amr and Amin[1] showed non-significant differences in male and female attainment in psychiatry in our institute. Our subjective impressions and a previous study suggested that women had more positive attitude and performed better than males in King Faisal University.…”
Section: Introductionmentioning
confidence: 71%
“…[11] OSCE is in use in many medical disciplines in Saudi Arabia, particularly in general surgery,[1213] orthopedics,[14] internal medicine, and psychiatry. [1]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations